Actinotignum Schaalii bacteremia: from microbiota to the infection - SARA PINTO; MARIA FIGUEIREDO; FATIMA LEAL-SEABRA; CATARINA Pereira (Sociedade Galega de Medicina Interna, 2019)
Actinotignum schaalii is a gram-positive, facultative anaerobic bacillus, an opportunist agent that is underestimated or mistaken as a contaminant. In this article, we present a case of sepsis with multiorgan dysfunction due to acute pyelonephritis complicated by A. schaalii bacteraemia in an elderly patient with diabetes mellitus, chronic obstructive renal disease, benign prostatic hyperplasia, renal lithiasis and chronic urinary device. Through specific laboratory techniques such as Matrix-Assisted Laser Desorption/Ionisation Time-Of-Flight Mass Spectrometry, it was possible to identify the presence of A. schaalii in blood cultures. However, uroculture was negative. After 20 days of β-lactam, it was possible to successfully heal the infection. The difficulty in identifying this rare agent has definitely constrained our diagnostic and therapeutic approach.